2006
DOI: 10.1038/labinvest.3700425
|View full text |Cite
|
Sign up to set email alerts
|

The antifibrogenic effect of (−)-epigallocatechin gallate results from the induction of de novo synthesis of glutathione in passaged rat hepatic stellate cells

Abstract: Hepatic stellate cells (HSC) are the major players during hepatic fibrogenesis. Overproduction of extracellular matrix (ECM) is a characteristic of activated HSC. Transforming growth factor-beta (TGF-b) is the most potent fibrogenic cytokine while connective tissue growth factor (CTGF) mediates the production of TGF-b-induced ECM in activated HSC. HSC activation and hepatic fibrogenesis are stimulated by oxidative stress. Glutathione (GSH) is the most important intracellular antioxidant. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 47 publications
(54 reference statements)
1
36
1
Order By: Relevance
“…The most prominent was the extremely high expression of IGFBP-5, which is known to be the most abundantly expressed protein in activated HSC. In addition, IGFBP-7 is obviously detected in these cells, whereas a smaller induction is seen for IGFBP-4, -6 and -3 [6] . The growth-promoting and metabolic activities of IGF-1 and -2 are modulated by the family of IGFBPs [23] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most prominent was the extremely high expression of IGFBP-5, which is known to be the most abundantly expressed protein in activated HSC. In addition, IGFBP-7 is obviously detected in these cells, whereas a smaller induction is seen for IGFBP-4, -6 and -3 [6] . The growth-promoting and metabolic activities of IGF-1 and -2 are modulated by the family of IGFBPs [23] .…”
Section: Discussionmentioning
confidence: 95%
“…In recent studies, HSC were the primary source of excess ECM assembly in liver fibrosis [5] . During the development of liver fibrosis, HSC undergo a process of activation, resulting in the expression of ECM, reduced retinoid storage capability and transdifferentiation to a myofibroblast-like phenotype which is characterized by expression of α-smooth muscle actin (α-SMA) [6] . Fibrotic changes result in structural changes and lead to reconstruction of hepatic lobules, dysfunction of liver bioactivity, and even death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EGCG suppresses the proliferation of hepatic stellate cells and production of extracellular matrix in the hepatic fibrosis (19)(20)(21). Yumei et al reported that EGCG induced the de novo synthesis of glutathione and antifibrogenic effects in passaged rat hepatic stellate cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…cells play a central role in hepatic fibrosis (21), and epigallocatechin gallate, the major green tea polyphenol catechin, has been shown to inhibit collagen production in these cells (17). It has also been demonstrated that epigallocatechin gallate inhibits activation of these cells by suppressing Rho signaling, suggesting its therapeutic potential in the setting of liver fibrosis (8).…”
Section: Figmentioning
confidence: 99%